Perkembangan Penelitian Indikator Kota Berkelanjutan Menggunakan Bibliometric Analysis dan Systematic Literature Review - Widyawati, Laili Fuji; Istiqomah, Asti; Yolamalinda, Yolamalinda (LPPM Universitas Terbuka, 2023)
The three pillars of sustainability namely economic, ecological, and social have been fundamental in development including sustainable urban development. A sustainable city is one that’s environmentally safe, socially inclusive, and economically viable, to allow all of its citizens, now or in the future, to meet their personal needs and improve their quality of life at no cost to others’ natures or human lives. Effective evaluation of urban sustainability is essential for sustainable development. In evaluating, it is necessary to measure sustainability indicators. Therefore, the goal of this study is to determine development and productivity of sustainable city research publications using bibliometric analysis and to identify indicators for evaluating the sustainability of a city using Systematic Literature Review (SLR). Data were obtained through search methods from the leading Scopus journal database and manual search. The material obtained is then filtered in three stages namely identifications, screening, and eligibility level. Based on the bibliometric analysis, it was identified that the word cloud of popular research keywords is sustainability and sustainable development while research with indicator keywords is still limited. As a result SLR, had a total of 36 materials and documents that were found and summarized for highlighting. The results showed that there were 225 indicators in a sustainable city, consisting of socio-cultural (65 indicators), environmental (75 indicators), economy (51 indicators), ICT/transverse (12 indicators), and urban (22 indicators) dimensions.